Accommodation Dispensing or Course Design Consulting?: Views and Experiences of Accessibility Consultants Contributing to Inclusive Course Redesigns in Postsecondary Education - Burge, Philip; Mazzuca, Josephine (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
There are growing demands to proactively support students with disabilities in postsecondary education. This article examines a mixed-methods study with accessibility consultants and other faculty in a community college pilot program focussed on redesigning courses to increase inclusiveness. Findings highlight the successful and well-received role of the accessibility consultants collaborating in redesign triads. Challenges experienced by accessibility consultants are also discussed, for example, around time allocation for this type of work along with their daily support of students. Recommendations for accessibility consultants involvement in expanding inclusive course redesigns are made, such as, including them more in the process of curriculum design and ensuring appropriate time for their participation.